Epidemiology of burns in a teaching hospital in south India - R. Raja Shanmugakrishnan; V. Narayanan; P. Thirumalaikolundusubramanian (Indian Journal of Plastic Surgery)
despite many medical advances, burns continue to remain a challenging problem due to the lack of infrastructure and trained professionals as well as the increased cost of treatment, all of which have an impact on the outcome. there is very little information on the pattern of outcomes among burn patients in relation to clinical aspects in india.hence, the present study was undertaken in a burns unit to determine selected epidemiological variables, assess the clinical aspects (etiology, extent and anatomical location) and first aid measures adopted and finally to analyse the outcomes in cases of burn injuries. in addition, we have sought to suggest measures to remove myths about pre-hospital burn treatment and provide recommendations to healthcare professionals.